Methanol Extracts Potential of Mas Ngur Shells (Atactodea striata) against Protease Profile and Description of Histopathology of Jejunum Rats Exposed by Indomethacin - Vivi Shofia; Celcius Waranmasalembun; Sasangka Prasetyawan; Aulanni'am Aulanni'am (Chemistry Department, The University of Brawijaya, 2015)
Inflammatory Bowel Disease (IBD) is a multi-factorial disorder caused by genetic factors, environmental and immune response. One of the causes of IBD is a side effect of non-steroidal of anti-inflammatory drugs (NSAIDs). Indomethacin is an NSAID that activates macrophages and triggers increasing of protease activity. Mas Ngur shells (Atactodea striata) contains an antioxidant that inhibits the protease activity. This research used rats (Rattus norvegicus) induced by Indomethacin and treated with methanol extract of Mas Ngur shells (A. striata) at doses of 100 and 400 mg/kg of body weight (BW). Therapy potency of the Mas Ngur shells methanol extracts were identified by measuring protease activity and observed the Jejenum histopathology. Statistical analysis showed that the Mas Ngur shells therapy showed significant differences (p <0.05) by decreasing of protease activity and improve jejunum histopathology of IBD induced rats